Schistosoma haematobium, Plasmodium falciparum infection and anaemia in children in Accra, Ghana - Nyarko, Ruth (Trop Dis Travel Med Vaccines, 2018)
BACKGROUND: Urinary Schistosomiasis and malaria are endemic in Sub-Saharan Africa. There are public health concerns and implications of these parasites. This study sought to assess the prevalence of malaria, urinary schistosomiasis, and anaemia in children of school going age in two municipalities in Ghana. METHODS: A cross-sectional study design was used to investigate the prevalence of S. haematobium, P. falciparum infection and the haemoglobin concentration of respondents. A total of 404 (231 males and 173 females) school children between ages 9 - 14 years (mean age 11.8 ± 1.4 years) were recruited for the survey. Urine and blood samples were collected using standard operating procedures for urinary schistosomiasis and malaria diagnosis. Haemoglobin concentration was measured using a Hemocue® Hb 201 m. RESULTS: The prevalence of mono-infection was 4.7 and 12.9% for S. haematobium and P. falciparum respectively with a small proportion (0.9%) of the respondents infected with both parasites. The prevalence of anaemia in the study population was 59.9%. The risk of developing anaemia was not associated with being infected with any of the parasites. All co-infected children had anaemia. CONCLUSION: High prevalence of anaemia was observed within the study population. Prevalence of malaria was higher compared to schistosomiasis. Interventions to address the high levels of anaemia is required within the community. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40794-018-0063-7) contains supplementary material, which is available to authorized users.